Resilience in Healthcare: A Hospital-based Investigation of Breast Cancer Diagnostics Amid the Pandemic in Indonesia - Choridah, Lina; Anwar, Sumadi Lukman; Heriyanto, Didik Setyo; Handoko, Alberta Vania; Sumoro, William; Icanervilia, Ajeng Viska; Rengganis, Anggraeni Ayu (http://dharmais.co.id/, 2024)
Background: Widespread disruptions in healthcare services have occurred due to ongoing challenges during the pandemic. The tremendous impacts have struck countries with limited resources, greater distances of geographical access to healthcare services, and a shortage of healthcare personnel. Long delay of diagnosis and disruption in patient care affects the long-term prognosis of breast cancer. This study was conducted to investigate the effects of the COVID-19 pandemic and government-mandated social restrictions on the provision of diagnostic services for breast cancer patients in a tertiary referral hospital. The study aimed to explore how travel restrictions and patients' apprehension about COVID-19 exposure have contributed to notable declines in diagnostic and treatment procedures for breast cancer within this healthcare setting. Methods: This study was retrospective design and used a hospital registry to collect information on demographics, imaging, and pathology from January 2018 to September 2021. Breast ultrasound (US) and mammography data were collected from the Picture Archiving and Communication System (PACS), while pathology data were collected from e-medical records. The descriptive statistics of the annual total volume of imaging and pathological examinations were interpreted and statistics were only calculated for diagnostics mammography. Results: Between 2018 and 2021, the volume of monthly breast sonograms drastically decreased by 65% in 2020 and 2021 during the pandemic, while mammography significantly reduced by more than 40% from the 2019 levels. Breast US and mammography procedures were significantly lower during the first and second waves of the pandemic in March until May 2020 and June until September 2021, respectively. Although the proportion of breast ultrasound-guided fine-needle aspiration biopsy (FNAB) increased year by year, the number of FNAB for primary breast lesions significantly decreased by 84% in 2020 and 2021. Conclusions: We observed significant decreases in diagnostic procedures for breast cancer. Reconfiguration of breast cancer care scheduling is required to accommodate the potential for increased hospital visits after the travel restrictions.